THE ACCURACY TRANSLATION OF ATTITUDE IN MAIN CHARACTER AT ANIMAL FARM NOVEL - Fedro Iswandi; M.R. Nababan; NFN Djatmika (Widyaparwa, 2020)
A translator has an important role to transfer messages from a source language into a target language accurately. Therefore, this research aims to analyze the translation accuracy of words, phrases, and clauses that accommodate attitude in two translators by using a systemic functional linguistics approach. The research used descriptive qualitative and comparative study. The data are words, phrases, and clauses that accommodate attitude. Then, the data were obtained through document analysis, focus group discussion. Next, data is analyzed with analysis of domain, taxonomic, componential, and cultural themes. The result shows that Bakdi used ten techniques; established equivalent, modulation, transposition, discursive creation, adaptation, generalization, implicit, reduction, explicit, and literal. Meanwhile, Mahbub used twelve techniques; established equivalent, modulation, discursive creation, generalization, amplification, variation, literal, explicit, reduction, transposition, particularization, description, etc. The last, accuracy in Bakdi is better than Mahbub. It can be influenced by some factors; the choosing of translation techniques, translator background, and context of a situation.Seorang penerjemah memiliki peran penting untuk menerjemahkan pesan dari bahasa sumber ke dalam bahasa sasaran dengan akurat. Oleh karena itu, penelitian ini bertujuan untuk menganalisis derajat keakuratan terjemahan kata, frasa dan klausa yang mengakomodasi sikap pada dua penerjemah dengan pendekatan linguistik sistemik fungsional. Penelitian ini adalah penelitian deskriptif kualitatif dan studi perbandingan. Data berupa kata, frasa dan klausa yang mengakomodasi sikap. Lalu, data diperoleh melalui analisis dokumen, focus group discussion. Selanjutnya, data dianalisis dengan analisis domain, taksonomi, komponensial dan tema budaya. Hasil menunjukkan bahwa Bakdi menggunakan 10 teknik penerjemahan; padanan lazim, modulasi, transposisi, kreasi diskursif, adaptasi, generalisasi, implisitasi, reduksi, eksplisitasi dan harfiah. Sementara, Mahbub menggunakan 12 teknik; padanan lazim, modulasi, kreasi diskursif, generalisasi, amplifikasi, variasi, harfiah, eksplisitasi, reduksi, transposisi, partikularisasi dan deskripsi. Terakhir, derajat keakuratan Bakdi lebih bagus dibandingkan Mahbub. Hal ini dipengaruhi oleh beberapa faktor seperti pemilihan teknik penerjemahan, latarbelakang penerjemah dan konteks situasi.